2017
DOI: 10.4025/actascihealthsci.v39i2.27789
|View full text |Cite
|
Sign up to set email alerts
|

<b>Histological and morphological evaluation of condylar cartilage of young rats in response to stimulation of mandibular protrusion

Abstract: ABSTRACT. The aim of this study was to evaluate the histogical and morphological aspects of the condyle in response to mandibular protrusion induced by composite resin occlusal planes. Thirty fiveweek-old male Wistar rats were selected and randomly divided in two groups. One group received a composite resin type of oclusal plane that induced mandibular protrusion, and the other was the control group, without treatment. Animals were euthanized after experimental time intervals of 7, 21 and 30 days. For histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, despite this variability, the aluminum splint was still able to create an observable amount of condylar process remodeling in at least half of the animals. The joints remodeled in a different manner compared to the RM group, probably owing to the fact that the aluminum splints used were thin anterior-posteriorly, so that the lower incisor teeth moved outside the occlusion plane of the splint during mastication and the incisor teeth were pushed protrusively or intrusively by the splints, similar to the setup in other studies ( Farias-Neto et al , 2012 ; Sá et al , 2017 ). This could be why there was a minimal amount of remodeling observed in two of the rats with aluminum splints, at least at the site analyzed, if the changes were primarily manifest in the anterior/posterior region.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Nevertheless, despite this variability, the aluminum splint was still able to create an observable amount of condylar process remodeling in at least half of the animals. The joints remodeled in a different manner compared to the RM group, probably owing to the fact that the aluminum splints used were thin anterior-posteriorly, so that the lower incisor teeth moved outside the occlusion plane of the splint during mastication and the incisor teeth were pushed protrusively or intrusively by the splints, similar to the setup in other studies ( Farias-Neto et al , 2012 ; Sá et al , 2017 ). This could be why there was a minimal amount of remodeling observed in two of the rats with aluminum splints, at least at the site analyzed, if the changes were primarily manifest in the anterior/posterior region.…”
Section: Discussionmentioning
confidence: 59%
“…However, there was no assessment of the joint contralateral to the splint in these studies, despite the possibility that bilateral changes that might be more reflective of the human condition. As for incisor splints, studies also have shown an impact on condylar process remodeling ( Farias-Neto et al , 2012 ; Ghafari and Degroote, 1986 ; Guo et al , 2020 ; Sá et al , 2017 ; Wang et al , 2018b ; Watanabe et al , 2008 ), but the effects observed were the same on both condylar processes. Therefore, the objective of this study was to compare the impact between different splint methods (incisor and molar) and materials (resin, aluminum, stainless steel) for altering the bite on the gross and histological appearance of the mandibular condylar processes of Sprague Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature points out that the condylar region may be subject to remodeling to the detriment of external stimuli due to the high adaptive capacity of the cartilaginous zones, which would result in the potential to manipulate the growth of the mandible [8][9][10][11][12]. Many studies have evaluated skeletal and dentoalveolar changes during mandibular advancement therapies for the treatment of Class II malocclusions due to mandibular deficiency [13][14][15][16][17][18][19] with the use of fixed and removable functional orthopedic devices due to their ability to stimulate the growth of the mandible, especially in the region of the condyle and the mandibular fossa, restricting the anterior displacement of the maxilla, in addition, to generate dentoalveolar effects [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies show that the anterior repositioning of the mandible can accelerate the maturation of chondrocytes in young animals [9,10,37,38] and reactivate chondrogenesis at rest in adult animals [10,39,40], inducing morphological and histological changes in the anterior and posterior region of the condyle, formation of cartilaginous matrix and consequent increase in endochondral ossification. However, there are divergences especially concerning the age limit of response to orthopedic-functional therapies [8,9,41].…”
Section: Introductionmentioning
confidence: 99%